C-tactile touch perception in migraineurs – a case-control study. (April 2020) - Lapp, Hanna Sophie; Sabatowski, Rainer; Weidner, Kerstin; Croy, Ilona; Gossrau, Gudrun
Background: Migraine is characterized by sensory hypersensitivity and habituation deficits. Slow brushing over the skin activates C-tactile nerve fibers, which mediate pleasant touch and analgesic effects in healthy subjects. As this function is altered in painful conditions, we aimed to examine whether the C-tactile processing is disrupted in migraines. Methods: To psychophysically assess C-tactile function, we applied optimal and suboptimal C-tactile stroking stimuli on the dorsal forearm (body reference area) and the trigeminally innervated skin of 52 interictal migraineurs and 52 matched healthy controls. For habituation testing, 60 repeated C-tactile optimal stimuli were presented in both test areas. The participants rated each stimulus on a visual analogue scale by intensity, pleasantness, and painfulness. Results: Regarding C-tactile function, migraineurs showed unphysiological rating patterns but no significantly different pleasantness ratings than controls. During repeated stimulation, controls showed stable pleasantness ratings while migraineurs' ratings decreased, especially in those experiencing tactile allodynia during headaches. Migraineurs taking triptans responded like controls. Conclusion: The C-tactile function of migraineurs is subclinically altered. Repeated C-tactile stimulation leads to altered habituation but differs from previous work by the direction of the changes. Although the pathophysiology remains unknown, causative mechanisms could include central and peripheral neuronal sensitization, tactile allodynia and hedonic stimulus attributions.